Entrepreneurial Intentions in Higher Education from the Analysis of Psychological, Human and Social Capitals: A Systematic Literature Review - Nofrans Eka Saputra; Johannes Johannes; Syahmardi Yacob; Tona Aurora Lubis (Universitas Ahmad Dahlan, 2024)
This systematic literature review provides a comprehensive exploration of the role of psychological, human, and social capital in shaping entrepreneurial intentions within the context of higher education. The study synthesizes findings from a wide range of empirical studies to assess how these capitals influence students’ aspirations to engage in entrepreneurial activities. An online search was conducted on 125 reputable articles in the 2012-2021 period on entrepreneur intention and psychological, human, and social capital. Our review encompasses a detailed analysis of the psychological constructs that motivate entrepreneurial intentions, such as personal attitude, perceived behavioral control, and subjective norms. Furthermore, we examine human capital elements, including education, skills, and experience, alongside social capital aspects like social networks and family support systems. This review highlights the complex interplay between individual capabilities and contextual factors by integrating insights from multiple theoretical frameworks, including the Theory of Planned Behavior and Social Cognitive Career Theory. The findings suggest that while psychological capital is crucial in forming entrepreneurial intentions, human and social capital are equally significant in providing the necessary resources and networks to act on these intentions. This review contributes to academic discourse by clarifying the roles and relationships of different types of capital in entrepreneurial intention formation among higher education students, offering implications for educators and policymakers in fostering a conducive entrepreneurial ecosystem.